2012
DOI: 10.1289/ehp.1103469
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Exposure to Residential Air Pollution and Infant Mental Development: Modulation by Antioxidants and Detoxification Factors

Abstract: Background: Air pollution effects on children’s neurodevelopment have recently been suggested to occur most likely through the oxidative stress pathway.Objective: We aimed to assess whether prenatal exposure to residential air pollution is associated with impaired infant mental development, and whether antioxidant/detoxification factors modulate this association.Methods: In the Spanish INfancia y Medio Ambiente (INMA; Environment and Childhood) Project, 2,644 pregnant women were recruited during their first tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
91
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 37 publications
6
91
4
3
Order By: Relevance
“…This sharp increase could be partly attributed to better diagnosis due to improved diagnostic criteria and increased awareness, but it cannot account for the exponential increase. Research studies into prenatal exposure to environmental contaminants such as pollution, proximity to highways, and maternal occupation, have acquired heightened interest as a possible role in the etiology of autism [55][56][57][58][59]. A recent study of identical twins reported that genetics accounted for only 38% of autism risk, with environmental factors explaining the remaining 62% [60].…”
Section: Discussionmentioning
confidence: 99%
“…This sharp increase could be partly attributed to better diagnosis due to improved diagnostic criteria and increased awareness, but it cannot account for the exponential increase. Research studies into prenatal exposure to environmental contaminants such as pollution, proximity to highways, and maternal occupation, have acquired heightened interest as a possible role in the etiology of autism [55][56][57][58][59]. A recent study of identical twins reported that genetics accounted for only 38% of autism risk, with environmental factors explaining the remaining 62% [60].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we did not consider the impact of other chronic and acute outcomes also potentially associated with near-road traffic-related pollution and/or regional urban pollution, such as asthma in adults, chronic pulmonary obstructive disease, cognitive development in children or reproductive outcomes [5,54]. Asthma is most likely under-diagnosed, thus the prevalence used to derive attributable cases may be too low [33].…”
Section: Discussionmentioning
confidence: 99%
“…Maternal smoking correlates with socio-economic factors such as education and income (Kabir et al, 2011;Laaksonen et al, 2005) and may contribute to this association. The earlier studies (Calderon-Garciduenas et al, 2011;Guxens et al, 2012;Siddique et al, 2011;Volk et al, 2011;Vrijheid et al, 2012;Windham et al, 2006) Odds ratios and 95% confidence intervals of neurodevelopmental outcomes by residential address-based NO x (black circles) and PM 10 (black hollow diamonds) levels. The spikes represent odds ratios for outcomes of interest and cap lines indicate 95% confidence intervals.…”
Section: Figurementioning
confidence: 99%